Efektivitas Senam Tera dan Terapi Akupresur pada Titik Taichong terhadap Penurunan Tekanan Darah pada Pasien Hipertensi di Desa Pedagangan Kecamatan Tiris Probolinggo - Indriwati Indriwati; Ainul Yaqin Salam; Alwin widhiyanto (STIKes Ibnu Sina Ajibarang, 2025)
Hypertension is a condition marked by elevated blood pressure, increasing risks of morbidity and mortality. Non-pharmacological treatments such as Tera exercise and acupressure therapy at the Taichong point offer alternative interventions. Tera exercise combines breathing techniques and body movements to reduce anxiety and promote vasodilation, thereby lowering blood pressure. Acupressure at the Taichong point facilitates energy flow, also contributing to blood pressure reduction. This study aims to compare the effectiveness of Tera exercise and Taichong point acupressure in lowering blood pressure among hypertensive patients. A two-group pre-post design was employed with a sample of 44 respondents selected through purposive sampling. Blood pressure data were collected using observation sheets. In the Tera exercise group (n=22), the average systolic pressure decreased from 148.77 mmHg to 143.77 mmHg, and diastolic pressure from 88.00 mmHg to 83.00 mmHg. In the acupressure group (n=22), systolic pressure reduced from 153.36 mmHg to 147.50 mmHg, and diastolic from 92.86 mmHg to 84.00 mmHg. Paired t-test analysis showed a significant difference (p-value = 0.000 < α = 0.05), indicating that acupressure therapy at the Taichong point is more effective in reducing blood pressure. This study concludes that while both therapies are effective, acupressure yields greater reductions and is recommended as a non-pharmacological treatment for hypertension in Trading Village, Tiris District, Probolinggo Regency.